2009
DOI: 10.1177/1087054709342212
|View full text |Cite
|
Sign up to set email alerts
|

Nonmedical Prescription Stimulant Use Among a Sample of College Students

Abstract: Continued research regarding psychological variables, specific group membership (e.g., fraternity, sorority, athletics), and stimulant acquisition is suggested. Effective prevention and education efforts are needed to help address the nonmedical use of prescription stimulants on college campuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
183
7
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(212 citation statements)
references
References 37 publications
21
183
7
1
Order By: Relevance
“…In fact, our data suggest that consumption of prescription drugs for enhancement by Australian university students is lower than that in the USA (McCabe et al 2005;Weyandt et al 2009;Wilens et al 2008) and more similar to that in Europe (Franke et al 2011;Mache et al 2012;Schelle et al 2015). Importantly, the results from this study also support previous CE usage prevalence estimates in Australian university student populations derived by Mazanov et al (2013).…”
Section: Discussionsupporting
confidence: 83%
“…In fact, our data suggest that consumption of prescription drugs for enhancement by Australian university students is lower than that in the USA (McCabe et al 2005;Weyandt et al 2009;Wilens et al 2008) and more similar to that in Europe (Franke et al 2011;Mache et al 2012;Schelle et al 2015). Importantly, the results from this study also support previous CE usage prevalence estimates in Australian university student populations derived by Mazanov et al (2013).…”
Section: Discussionsupporting
confidence: 83%
“…Another survey at a large, public, southeastern university found that, of the 1811 student participants, 34% had used ADHD medications nonmedically (DeSantis et al, 2008). A sample of 390 college students found that 7.5% had used prescription stimulants for nonmedical purposes within the past 30 days (Weyandt et al, 2009). Questionnaires collected from 381 students at a midwestern university revealed that 13.7% of participants (17% of men, 11% of women) had taken stimulants for nonmedical purposes (Hall et al, 2005).…”
Section: Methylphenidatementioning
confidence: 99%
“…The increase in stimulant prescriptions has resulted in a corresponding escalation of illicit use, particularly in college students, confirmed by numerous survey results (Advokat et al, 2008;Arria & DuPont, 2010;Hall et al, 2005;McCabe et al, 2005;Rabiner et al, 2008;2009a, 2009bRabiner et al, 2010;Teter et al, 2003;Teter et al, 2005;Teter et al, 2006;Weyandt et al, 2009;White et al, 2006;Wilens et al, 2008). Wilens and colleagues (2008) report lifetime rates of diversion ranging from 16 to 29%, with medical prescriptions being given, sold or traded by students.…”
mentioning
confidence: 92%